A meta-analysis of cognitive and functional outcomes in severe brain trauma cases - Shuanglong, Zhang; Jiangyuan, Yuan; Meng, Nie; Zheng, Wang; Yunshui, Zhang; Wei, Sun; Li, Qiao; Rongcai, Jiang (Frontiers in Behavioral Neuroscience, 2024)
Background: Globally, severe traumatic brain injuries (TBI) are an important health issue, which is associated with harmful side effects. This meta-analysis investigates the cognitive and functional outcomes in severe brain trauma cases. It assesses the impact on memory, verbal and visual abilities, attention, learning, and the presence of depression. The study provides a comprehensive overview of the consequences of severe brain trauma on cognitive and functional domains. Objective: The main objective of the current comprehensive meta-analysis study is to assess and analyze the impact of severe TBI on functional and cognitive outcomes, including verbal, visual, attention, learning, memory and emotional stability. Methods: We collected data from three online databases, including PubMed, Cochrane Library and Embase. Case-control trials related to severe TBI association with cognitive and functional outcomes were included. Verbal strength, visual functions, learning abilities, attention, memory and depression were considered as primary outcomes. Results: We have included 13 case-control studies with 1442 subjects in this meta-analysis, which provide adequate data to determine pooled effect size for targeted outcomes. Effect of severe TBI on inducement of depression and impairment of memory, verbal, visual, attention and learning abilities compared to the control group showed statistically significant outcomes (P < 0.05) Conclusion: Severe TBI is strongly associated with impaired cognitive and functional abilities, including visual and verbal disabilities, impaired memory, depression inducement, attention deficit and learning disabilities.